Estudos de blendas poliméricas com aplicações em células eletroquímicas emissoras de luz (LEC) - Araújo, Estácio Paiva de (2017)
In this work polymer blends were studied, which were capable of being the active layer in Light Emitting Cell (L.E.C.). The materials chosen for the formation of the active layer were the poly[2-methoxy-5-(2′-ethylhexyloxy)-1,4-phenylenevinylene]- MEH-PPV and the Poli(2,5-bis(2'-ethyl-hexyl)-1,4-phenylenevinylene]- BEHP-PPV and two systems polymer electrolytes, poly (ethylene oxide) block polyethylene (PE-b-POE), complexed with inorganic salts, Lithium Perchlorate (LiClO4) † and Lithium Triflate (LiCF3SO3). To obtain the blends, the solutions of polymer electrolytes were prepared in acetonitrile and the conjugated polymer were prepared in THF. The salt concentration was varied in the range of 6,5%, 7,5% and 8,5%. The results show that the optical properties, absorption and emission, of the BEHP-PPV blends are more modified with the presence of the electrolytes then the MEH-PPV systems. However, in the MEH- PPV blends the vibrational modes of salt dissociated weren’t observed, suggesting high aggregation proven surface measurements. The AFM images help us confirm the phase separation of the blends. IxV curves reveal that BEHP-PPV blend of 8,5% with Lithium Perchlorate optimized the current and negative resistance effects are also observed in this LEC.